Suppression of chikungunya virus replication and differential innate responses of human peripheral blood mononuclear cells during co-infection with dengue virus. - Mariana Ruiz Silva; José A Aguilar Briseño; Vinit Upasani; Heidi van der Ende-Metselaar; Jolanda M Smit; Izabela A Rodenhuis-Zybert (Public Library of Science (PLoS), 2017)
Dengue and chikungunya are viral diseases transmitted to humans by infected Aedes spp. mosquitoes. With an estimated 390 million infected people per year dengue virus (DENV) currently causes the most prevalent arboviral disease. During the last decade chikungunya virus (CHIKV) has caused large outbreaks and has expanded its territory causing millions of cases in Asia, Africa and America. The viruses share a common mosquito vector and during the acute phase cause similar flu-like symptoms that can proceed to more severe or debilitating symptoms. The growing overlap in the geographical distribution of these mosquito-borne infections has led to an upsurge in reported cases of DENV/CHIKV co-infections. Unfortunately, at present we have little understanding of consequences of the co-infections to the human host. The overall aim of this study was to define viral replication dynamics and the innate immune signature involved in concurrent DENV and CHIKV infections in human peripheral blood mononuclear cells (PBMCs). We demonstrate that concomitant infection resulted in a significant reduction of CHIKV progeny and moderate enhancement of DENV production. Remarkably, the inhibitory effect of DENV on CHIKV infection occurred independently of DENV replication. Furthermore, changes in type I IFN, IL-6, IL-8, TNF-α, MCP-1 and IP-10 production were observed during concomitant infections. Notably, co-infections led to a significant increase in the levels of TNF-α and IL-6, cytokines that are widely considered to play a crucial role in the early pathogenesis of both viral diseases. In conclusion, our study reveals the interplay of DENV/CHIKV during concomitant infection and provides a framework to investigate viral interaction during co-infections.